ANALISIS LIKUIDITAS PADA KOPERASI WANITA SEULANGA KABUPATEN ACEH TIMUR - Afnina (FEBI IAIN Langsa, 2019)
The ability to pay for an organization can only be known after comparing the power of paying an organization on the one hand with ﬁ nancial obligations that must immediately be fulﬁ lled on the other. In this study, we want to know the ﬁ nancial condition of a women’s cooperative in Southeast Aceh in terms of its liquidity aspects based on current ratio, quick ratio and cash ratio measurement tools. Liquidity is the ability of a business to meet all obligations, both to maintain the continuity of business operations and to pay its debts without disrupting the smooth running of the business. Based on the results of the study, it is known that the business activities carried out by the cooperative are savings and loans with the service calculation of 3% per annum system. The member who borrowed partly stalled in repayment. Nevertheless the level of liquidity can still be maintained. Based on the results of data processing it is known that the ﬁ nancial condition of the Seulanga Women’s Cooperative in East Aceh Regency in terms of its liquidity, liquidity and ability to cover its current liabilities, is evident from the current ratio value of 4.66: 1, quick ratio of 4.58: 1, and cash ratio 1.78: 1 that is able to guarantee every 1 rupiah or 100% of its current debt, or current assets can guarantee its current debt. From this explanation it can be said that the hypothesis that the alleged Seulanga Women’s Cooperative in East Aceh Regency is able to control its level of liquidity is acceptable and proven. So it is suggested to this cooperative to always utilize every rupiah of its assets properly, so as to maintain and maintain the level of liquidity.